Surface modification of GO/TiO2 thin film by sodium dodecyl sulphate for photocatalytic applications - Che Halin, Dewi Suriyani; Azani, Azliza; Mohd Salleh, Mohd Arif Anuar; Abdul Razak, Kamrosni; Al Bakri Abdullah, Mohd Mustafa; Ramli, Muhammad Mahyiddin; Vizureanu, Petrica; Abdul Razak, Mohd Fairul Sharin; Mohamad, Noraiham (The Minerals, Metals & Materials Society, 2024)
Photocatalyst material titanium dioxide (TiO2) and graphene oxide (GO) were used to improve the self-cleaning properties of thin films. The sol–gel spin-coating method was successfully used to synthesize GO/TiO2 thin films. Surface modification was applied to optimize the self-cleaning capabilities by adding several concentrations of sodium dodecyl sulfate (SDS) (0.1 w/v%, 0.2 w/v%, 0.3 w/v%, 0.4 w/v%, and 0.5 w/v%) to the parent solution. The synthesized thin films were investigated using scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray diffraction, UV-visible spectroscopy, water contact angle analysis, and photocatalytic analysis. The AFM and SEM images revealed that as the SDS amount increased, the particles became less agglomerated, and the roughness of the surface reduced from 2.54 × 102 nm to 0.83 × 102 nm. The wettability analysis showed that when SDS increased to 0.4 w/v%, the water contact angle dropped to 15.30°, implying that the thin film exhibits hydrophilic qualities. A decrease in the GO/TiO2 band gap was obtained linearly with the increase in SDS addition from 3.17 eV to 2.75 eV. Finally, the improvement of the surface coating and reduction of the band gap enhanced the photocatalytic activity, which degraded 78.97% of methylene blue, which was obtained by 0.4SDS.